Six‐year follow‐up of the initial Dutch subcutaneous implantable cardioverter‐defibrillator cohort: Long‐term complications, replacements, and battery longevity. (20th April 2018) - Quast, Anne‐Floor B. E.; van Dijk, Vincent F.; Yap, Sing‐Chien; Maass, Alexander H.; Boersma, Lucas V. A.; Theuns, Dominic A.; Knops, Reinoud E.
Abstract: Introduction: Experience with the subcutaneous implantable cardioverter‐defibrillator (S‐ICD) is expanding rapidly. However, data on long‐term performance or complications related to elective generator replacement are lacking. Methods: Follow‐up (FU) data of all patients implanted between December 2008 and April 2011 were collected. Complications were defined as those requiring surgical intervention. Kaplan‐Meier estimates for complication and shock rates, with corresponding 95% confidence intervals (CI), were calculated. Results: One hundred and eighteen patients were included. Median FU was 6.1 years (IQR 5.6–6.5 years). Short‐term complication rate (0–30 days) was 3% (CI 0–6%). Long‐term complication rate at 6 years was 19% (CI 12–26%), corresponding with an annual complication rate of 3%. One patient in this cohort developed a need for a transvenous ICD (TV‐ICD) in order to provide pacing for bradycardia (1%). Six patients were implanted with a TV‐ICD after experiencing an S‐ICD complication for which extraction was necessary. In total, 10 S‐ICDs were extracted; none resulted in a complication. Eight patients had a nonsystemic ICD‐related infection and no lead failures were observed. The majority, 68 (58%) patients, received an elective generator replacement. Two patients had a complication related to generator replacement (3%). Battery longevity was 5.6 years (IQR 5.2–6.1). Appropriate and inappropriate shock rates of 6‐year estimates were 17% (CI 9–25%) and 21% (CI 15–27%), respectively. Conclusions: This cohort represents the longest follow‐up to date and shows a low annual complication rate without lead failures or systemic infections. Battery longevity of the first S‐ICD generation results in relative early generator replacement procedures.